Analysis of Student Interest in Natural and Social Sciences Integration Learning (IPAS): Study of Grade IV Students at SDN 8 North Metro - Alfarisi, Muhamad; Prasasti, Adya Rosa; Sarwendah, Titin (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This research investigated the engagement of fourth-grade students in Integrated Science and Social Studies (IPAS) learning at SDN 5 North Metro. Findings revealed that a significant majority of students (21 out of 25) exhibited high levels of engagement, characterized by enthusiastic participation, focused attention, and a strong desire to learn. These students demonstrated resilience in overcoming challenges, actively sought clarification, and displayed positive learning habits. The teacher played a crucial role in fostering student engagement through the implementation of diverse and engaging instructional strategies, including creative learning activities and a well-structured reward system. However, a small subset of students (4 out of 25) displayed lower levels of engagement, struggling with complex concepts and finding IPAS learning less interesting. This research highlights the importance of creating a dynamic and inclusive learning environment that caters to the diverse needs and learning styles of all students. Strategies such as connecting abstract concepts to real-world applications and incorporating more flexible learning approaches are crucial to enhance the engagement and understanding of all students in IPAS learning.